Plan para implementación de centros de recuperación de rsu aprovechables Machala, El Oro. - Lapo Moreno, John Cristhian (My University, 2021)
The purpose of this investigative work is to propose the plan for the implementation of MSW recovery centers in the city of Machala, due to the inconsistencies presented by the solid waste management system managed by the municipality and the lack of environmental awareness on the part of the citizenship. This was evidenced through a field investigation in which it led to technical visits to the Ceibales landfill, surveys directed at the population, and directors and technicians of the EMAM EP, in turn, interviews were conducted with the main recyclers of the city. In addition, for a correct development and elaboration of the project, the methods of abductive analysis, inferential statistics and bibliographic research were used. The main results of this plan are to improve the quality of life of the inhabitants of the Machalean city, reduce the amount of waste destined for final disposal, and promote the joint participation of the community and competent authorities for the preservation of the environment.
El presente trabajo investigativo tiene como finalidad proponer el plan de implementación de centros de recuperación de RSU en la ciudad de Machala, debido a las inconsistencias que presenta el sistema de gestión de residuos sólidos que maneja la municipalidad y la falta de conciencia ambiental por parte de la ciudadanía. Esto se evidenció a través de una investigación de campo en la cuál conllevó a realizar visitas técnicas al relleno sanitario Ceibales, encuestas dirigidas a la población, y a directores y técnicos de la EMAM EP, a su vez se realizaron entrevistas a las principales recicladoras de la ciudad. Además, para un correcto desarrollo y elaboración del proyecto se emplearon los métodos de análisis abductivo, estadístico inferencial e investigación bibliográfica. Con este plan se espera obtener como resultados principales mejorar la calidad de vida de los habitantes de la ciudad machaleña, reducir la cantidad de residuos destinados a disposición final, y promover la participación conjunta de la comunidad y autoridades competentes para la preservación del medio ambiente.
Keywords: RECUPERACION; RESIDUO SOLIDO